THE CORRELATION BETWEEN STUDENTS’ GRAMMAR MASTERY AND SPEAKING ABILITY AT THE ELEVENTH GRADERS OF SMA FRATER DON BOSCO MANADO - Lesirollo, Tiara; Pelenkahu, Noldy; Liando, Nihta V.F (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The role of grammar in language development is crucial as it exerts control over all aspects of communication. The objective of this study was to investigate the correlation between grammatical proficiency and verbal fluency. This study employed the descriptive approach. This study focused on eleventh-grade students from Frater Don Bosco Senior High School in Manado. A total of 35 pupils were included in the sample, and a random selection approach was utilised. The instruments comprised a grammar examination and an interview. The grammar exam aimed to evaluate the students’ proficiency in comprehending and applying grammatical rules to various test questions, whereas the interview examination aimed to measure the students’ English vocabulary and oral communication skills. The study’s findings indicate that eleventh-graders at Frater Don Bosco Senior High School in Manado had a limited proficiency in the language. The mean score of 68.57 indicated that the learners’ speaking skill was classified as fair. Based on the mean score (70.28). There was a strong correlation between students’ proficiency in grammar and their oral communication skills (rxy = 0.615; rxy (0.615) > r table) (0.344). The eleventh-grade students at Frater Don Bosco Senior High School in Manado demonstrated a positive and statistically significant correlation between their mastery of grammar and their proficiency in spoken language.